Application of Bioinformatics in the Internet of Things-Construction of Mushroom Cloud Digital Learning Platform. Issue 1 (April 2021) - Lin, Yu-Feng; Lin, Chia-Hui; Tsai, Sheng-Hsien; Lin, M-F(Fanny)
Abstract: In recent three years, the practical spirit of "DIY(Do-It-Yourself)"advocated in European and American education to combine the value of creativity and innovation is developed to a word "Maker" after integrating into the education system, which comes from the idea of "Hacker" and "Self-creator". The Maker transforms one-way learning model of "listening" and "writing" in the past to school curriculum of "image" and "practice", causing a reversal of traditional educational concepts. Educational policy in Taiwan naturally moves with the tide of the world. What characteristics of DIY, trouble-shooting, creativity sharing and community link emphasized by the Maker is in consistent with the transformation of technical and vocational education and the innovation of higher education that focus on the spirit of exploration and practice as well as innovation? The school used to participate in High Scope Program Phase II, including the development of "eco-art" course module for the first three years focused on plant observation along with the use of photography, presenting the idea of truth, goodness and beauty with the practice of "scientific drawing" in Fine Art Department; and, elaboration and promotion stage for the following two years focused on the reinforcement of introduction to biological course and the function of "online plants learning platform", expanding to university and senior high schools, including of the Affiliated Chongli Senior High School of National Central University, Taishan and Sanming Senior High School for the development of more functions. As the theme of mushroom nutrition & health care, the school continues the spirit of exploration and practice by integrating Dept. of Home Economics' food safety issues, Dept. of Chemistry's extraction analysis, Dept. of Physics' spectrograph analysis and Dept. of Computer Science's internet of things(IoT) into curriculum framework to develop courses module for additional learning platform of mushroom classification based on "online learning platform" within application of bioinformatics in the IoT. The content for logic concept of plant retrieval classification and feature concept of fungi classification is processed in our Mushroom Digital Learning Platform by combining tablet PC and interactive web pages of "Online plants and herbs(mushroom) learning platform" for multiple assessment, in order for teachers to understand the learning effect of each student and analyze the data through the cloud platform.